2016
DOI: 10.1002/acs.2734
|View full text |Cite
|
Sign up to set email alerts
|

Iterative learning control for non‐repetitive trajectory tracking of robot manipulators with joint position constraints and actuator faults

Abstract: SummaryIn this work, we present a novel iterative learning control (ILC) scheme for a class of joint position constrained robot manipulator systems with both multiplicative and additive actuator faults. Unlike most ILC literature that requires identical reference trajectory from trail to trail, in this work the reference trajectory can be non‐repetitive over the iteration domain without assuming the identical initial condition. A tan‐type Barrier Lyapunov Function is proposed to deal with the constraint requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Researchers worked hard to solve the initial problem of ILC for long [1], and only a few results were reported [2], [16]- [19], including time-varying boundary layer, initial rectifying action, error-tracking strategy, and so on. As far as the initial problem of robot ILC is concerned, the related results are very few [20], [21]. Jin used the initial rectifying action to handle the initial problem of robotic systems [20].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers worked hard to solve the initial problem of ILC for long [1], and only a few results were reported [2], [16]- [19], including time-varying boundary layer, initial rectifying action, error-tracking strategy, and so on. As far as the initial problem of robot ILC is concerned, the related results are very few [20], [21]. Jin used the initial rectifying action to handle the initial problem of robotic systems [20].…”
Section: Introductionmentioning
confidence: 99%
“…Note also that the desired trajectories x d, k ( t ) and y d, k ( t ) are iteration dependent. This extends the applications of most traditional ILC algorithms, which require identical reference trajectories over the iteration domain . At the start of each operation, ie, t = 0 at the k th iteration, x k (0) and y k (0) can be any values, which means they do not need to satisfy the common assumptions regarding the initial conditions in the ILC literature such as i.i.c.…”
Section: Discussion On Output Constraints Nonrepetitive Trajectoriesmentioning
confidence: 93%
“…The situation where the tracking tasks slowly vary with respect to iteration was tackled earlier in [2], and the robustness has been characterized for D-type, PD-type and PID-type learning algorithms. The non-equal task problem was addressed in the framework of AILC [14]- [16]. It is found that for the parameter learning, the reference signals are allowed to be vary with iteration, and the controller design can be carried out with ease.…”
Section: Introductionmentioning
confidence: 99%